Effects of Shared Story Reading in Mathematics for Students With Academic Difficulty and Challenging Behaviors. (September 2017) - Whitney, Todd; Lingo, Amy S.; Cooper, Justin; Karp, Karen
The primary focus of this study was to examine the effects of Shared Story Reading (SSR) during mathematics instruction on the behavioral outcomes of four elementary students with academic difficulty and challenging behaviors. In addition, the study examined the effect of implementing SSR during mathematics instruction on the teacher's use of opportunities to respond (OTR). A multiple baseline design across participants was implemented to examine the effects of this curricular approach on increasing the teacher's OTR, increasing student engagement, and reducing disruptive behavior. Results indicated there was an increase in OTR during the SSR lessons and suggest implementing SSR during mathematics instruction was effective for increasing engagement for students with academic difficulty and challenging behaviors. Results were not definitive regarding the effects of SSR decreasing disruptive behavior.